An explainable model of host genetic interactions linked to COVID-19 severity - Anthony Onoja; Nicola Picchiotti; Chiara Fallerini; Margherita Baldassarri; Francesca Fava; GEN-COVID Multicenter Study; Francesca Colombo; Francesca Chiaromonte; Alessandra Renieri; Simone Furini; Francesco Raimondi (Communications Biology, 2022)
A multifaceted computational strategy identifies 16 genetic variants contributing to increased risk of severe COVID-19 infection from a Whole Exome Sequencing dataset of a cohort of Italian patients.